Molecule‐Based Transistors: From Macroscale to Single Molecule. Issue 6 (3rd November 2020) - Li, Peihui; Jia, Chuancheng; Guo, Xuefeng
Abstract: Molecule‐based field‐effect transistors (FETs) are of great significance as they have a wide range of application prospects, such as logic operations, information storage and sensor monitoring. This account mainly introduces and reviews our recent work in molecular FETs. Specifically, through molecular and device design, we have systematically investigated the construction and performance of FETs from macroscale to nanoscale and even single molecule. In particular, we have proposed the broad concept of molecular FETs, whose functions can be achieved through various external controls, such as light stimulation, and other physical, chemical or biological interactions. In the end, we tend to focus the discussion on the development challenges of single‐molecule FETs, and propose prospects for further breakthroughs in this field. Abstract : This personal account introduces our recent works in the construction and performance of molecule‐based FETs from macroscale to nanoscale and even single molecule.